Design of web-based drug data management information system with codeigniter in Pharmacy Restu II. - Patrisia Fatima Jaya; Dimas Prasetyo Tegar Asmoro; Asih Septia Rini (Yayasan Bina Internusa Mabarindo, 2022)
Currently in the field of development architects using manual calculations is a business entity engaged in the field of pharmacy. The pharmacy Restu II which currently does not use information systems in managing its data. In this pharmacy, drug data management still uses manual means, namely using paper or book media in data storage, transaski process, recording of drug supplies and reports. The purpose of this research is to produce a computerized system to assist Pharmacy Restu II in managing and presenting data quickly, precisely and accurately and assisting the public in a more optimal transaction service process. In its creation the author uses web-based programming with PHP and MySQL programming languages with waterfall method. The results of this study aim to realize the creation of a computerized system at Pharmacy Restu II so that the management of drug data in pharmacies can run well.